Prediction of Forest and Land Rehabilitation Impacts on Peak Discharge, Erosion, and Sedimentation Reduction in The Piloliyanga Micro Catchment, Modelomo Watershed - Dicky Artha; Iswan Dunggio; Sukirman Rahim (West Science Social and Humanities Studies, 2026)
Watershed degradation contributes to increased peak discharge, erosion, and sedimentation in downstream areas. Forest and Land Rehabilitation (FLR) has become an important approach for restoring hydrological functions through increasing vegetation cover and controlling surface runoff. This study aimed to analyze the predicted impacts of FLR on peak discharge, erosion, and sedimentation in the Piloliyanga micro-catchment, Modelomo Watershed. The study employed a quantitative descriptive approach based on Geographic Information Systems (GIS), hydrological analysis, and land cover change simulation. Erosion analysis was conducted using the Universal Soil Loss Equation (USLE), while sedimentation was estimated using the Sediment Delivery Ratio (SDR) approach. The results showed that FLR has the potential to reduce peak discharge, erosion, and sedimentation through increased infiltration and vegetation interception. The novelty of this study lies in the integration of USLE, SDR, and land cover change simulation within a tropical micro-catchment watershed scale. The findings imply that watershed-based vegetative rehabilitation can improve hydrological stability and support land degradation control in the upstream area of the Modelomo Watershed.